Biosorption of oxytetracycline from water using moringa oleífera shells - Olivera, Agustina de (2020)
Pharmaceuticals as emerging contaminants have become a new threat to human life. Over the years, the amount of antibiotics and anti-inflammatory drugs has increased in rivers, lakes, oceans, and even in drinking water streams. The wastewater treatment plants (WWTPs) lack the necessary technology to remove a concentration within the range ng/l-mg/l and therefore, the need to develop effective, low cost and environmental friendly methods arise. Biosorption is a separation process, used in the area of Chemical Engineering, that follows the same fundaments of adsorption except for the use of biodegradable materials as adsorbent (biosorbent). This work focuses on studying the main optimal process conditions and the adsorption capacity of Moringa oleífera (MO) shells to remove Oxytetracycline (OTC). MO is recognized due to its anti-microbial, nutritional and coagulant properties; meanwhile, OTC is one of the most used antibiotics within the veterinary area.